INTRODUCTION STUDY OF MDR STAPHYLOCOCCUS AUREUS IN PIG SLAUGHTER HOUSE IN KUPANG CITY - Sanam, Maxs U. E.; Kallau, Novalino H. G.; Sitompul, Yeremia Y. (JURNAL KAJIAN VETERINER, 2022)
Due to the unprudent use of antibiotics globally, it causes the incidence of antibiotic resistance with the emergence of bacteria that are resistant to antibiotics and has implications for the failure of the use of antibiotics in dealing with various cases of diseases caused by bacteria. The incidence of antibiotic resistance in the livestock sector occurs due to the use of antibiotics that are not based on recommendations and antibiotics are given in the long term. The presence of bacteria that carry resistance to one or several kinds of antibiotics in livestock is a threat to animal and human health. The city of Kupang as an area that has pig farms and a high pig population has a big challenge to the emergence of antibiotic resistance due to the use of antibiotics in maintaining livestock health. One of the bacteria that has a large number of distributions and is widely found in livestock and is an indicator of antibiotic resistance is Staphylococcus aureus (S. aureus). This research has used an observational research method based on data collection methods and laboratory examinations, which are adjusted to the objectives that have been set. The approach that has been used in this research is a Cross Sectional Study, because it wants to get an overview of S. aureus bacteria that are resistant to antibiotics. The sample that has been needed is pig feces obtained by field observations. The data analysis technique that has been used is a descriptive analysis model, to explain the presence of antibiotic-resistant S. aureus bacteria in pig farms. The results showed that this isolation and identification process resulted in 28 (51.85%) samples that were positive for S. aureus. The highest prevalence of resistance was found in S. aureus which was resistant to the antibiotic Colistin sulfate (82.1%). The number of antibiotics tested from S. aureus isolates showed various variations from 0 to 3 types of antibiotics that were resistant in 1 isolate. The most common resistance pattern shown in S. aureus isolates was the CS (Colistin sulfate) pattern as many as 19 of the 28 samples. The conclusion of this study encourages the need to increase supervision related to the use of antibiotics and increase public awareness of the use of antibiotics and prevention of the increasing incidence of antibiotic resistance.